2010
DOI: 10.1007/s00432-010-0813-z
|View full text |Cite
|
Sign up to set email alerts
|

Perineural invasion in carcinoma of the cervix uteri—prognostic impact

Abstract: Perineural invasion is seen in about one-third of patients with cervical carcinoma. Patients affected by PNI represented a decreased overall survival. Further studies are required to get a deeper insight into the clinical impact and the pathogenetic mechanisms of PNI in CX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
1
31
1
1
Order By: Relevance
“…PNI and large tumor size were independent predictors of poor outcome in patients without LN invasion (Po0.05) (21). In another study on PNI in cervical cancer (IB1-IIB), 35.1% of patients (68 of 194 cases) had PNI (22). The presence of PNI was associated with stage, depth of invasion, and pelvic LN invasion (22).…”
Section: Perineural Invasion In Cervical Cancermentioning
confidence: 93%
See 3 more Smart Citations
“…PNI and large tumor size were independent predictors of poor outcome in patients without LN invasion (Po0.05) (21). In another study on PNI in cervical cancer (IB1-IIB), 35.1% of patients (68 of 194 cases) had PNI (22). The presence of PNI was associated with stage, depth of invasion, and pelvic LN invasion (22).…”
Section: Perineural Invasion In Cervical Cancermentioning
confidence: 93%
“…In another study on PNI in cervical cancer (IB1-IIB), 35.1% of patients (68 of 194 cases) had PNI (22). The presence of PNI was associated with stage, depth of invasion, and pelvic LN invasion (22). However, PNI reduced 5-yr OS, but 5-yr DFS was not different (22).…”
Section: Perineural Invasion In Cervical Cancermentioning
confidence: 94%
See 2 more Smart Citations
“…However, most studies agree that PNI of cervical cancer is strongly associated with a number of risk factors and associated with poor prognosis of cervical cancer (26). Horn et al (27) reported that PNI was associated with post-operative tumor stage, cervical stromal invasion, and pelvic lymph node metastasis in early cervical cancer patients. The authors also identified that the 5-year survival rate of cervical cancer patients with PNI was significantly lower than that of patients with negative PNI.…”
Section: Discussionmentioning
confidence: 99%